Pengaruh Fraud Diamond Terhadap Financial Statement Fraud (Studi Terhadap Perusahaan Anggota Indeks Sri-Kehati Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020) - Salmaa Ummu Kultsum; Dedik Nur Triyatno (UNIVED Press, 2022)
Financial statement is the document containing information that describes the company's financial condition and reflects the actual state of the company. Thus, it makes the management trying to produce financial statements describing that the company is in a healthy condition. However, management performance is sometimes not as good as expected. This encourages management to commit fraudulent financial statements. This study aims to determine the effect of the fraud diamond variables, namely pressure, opportunity, rationalization, and capability on financial statement fraud in SRI-KEHATI index member companies listed on the Indonesia Stock Exchange in 2016-2020. The sample selection technique used purposive sampling technique in order to obtain a sample of 70 companies. The data analysis technique used is descriptive statistical analysis and panel data regression using Eviews 12 software. The results of the study showed that the variables of pressure, opportunity, rationalization, and capability simultaneously had an influence on the financial statement fraud. The results of the study partially showed that the variables of financial stability, financial target, external pressure had a positive influence on the financial statement fraud. Meanwhile, the nature of industry had a negative influence on the financial statement fraud. Ineffective monitoring, change in auditor, and change in director variables had no influence on financial statement fraud.